Development of resistance in candida tropicalis : an in vitro study - J. Santhanam,; Fairuz A,; Ooi KF,; Muhamad Husni A., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
A study was conducted to determine the development of resistance in Candida tropicalis against antifungal agents after long-term exposure to low drug concentrations. Five clinical isolates of Candida tropicalis were selected for this study. These isolates were found to have already shown resistance to either amphotericin B or to fluconazole. Two isolates that were sensitive to fluconazole were exposed to 0.5 ?g/ml of fluconazole in a broth culture (Sabouraud dextrose broth) with frequent subculturing for up to 14 weeks. Three isolates that were sensitive to amphotericin B were exposed to 0.25 – 0.5 ?g/ml of amphotericin B in the same way. At different time intervals, the MIC values of the isolates were determined by the broth microdilution test as proposed by the National Committee for Clinical Laboratory Standards (NCCLS). Our results showed a 4-fold increase in the MIC values after 10 weeks of exposure to the antifungal agent, which continued to rise until the end of the experiment. Control isolates not exposed to antifungal agents showed no increase in their MIC values. Protein profiles of all isolates (using sodium dodecyl sulphate polyacrylamide gel electrophoresis) were obtained before and after exposure to antifungal agent. A change in the protein profile (new fractions or increased concentration) was observed for all isolates. In conclusion, induction of resistance was observed in Candida tropicalis isolates exposed to antifungal agents and this occurrence correlates with a change in the protein profile.